Toward a research agenda for competency-based medical education. (3rd June 2017) - Gruppen, Larry; Frank, Jason R.; Lockyer, Jocelyn; Ross, Shelley; Bould, M. Dylan; Harris, Peter; Bhanji, Farhan; Hodges, Brian D.; Snell, Linda; ten Cate, Olle; ,
Abstract: Competency-based medical education (CBME) is both an educational philosophy and an approach to educational design. CBME has already had a broad impact on medical schools, residency programs, and continuing professional development in health professions around the world. As the CBME movement evolves and CBME programs are implemented, a wide range of emerging research questions will warrant scholarly examination. In this paper, we describe a proposed CBME research agenda developed by the International CBME Collaborators. The resulting framework includes questions about the meaning of key concepts of CBME and their implications for learners, faculty members, and institutional structures. Other research questions relate to the learning process, the meaning of entrustment decisions, fundamental measurement issues, and the nature and definition of standards. The exploration of these questions will help to solidify the theoretical foundation of CBME, but many issues related to implementation also need to be addressed. These pertain to, among other things, nurturing independent learning, assembling and using assessment results to make decisions about competence, structuring feedback, supporting remediation, and how best to evaluate the longer-term outcomes of CBME. High-quality research on these questions will require rigorous outcome measures with strong validity evidence. The complexity of CBME necessitates theoretical and methodological diversity. It also requires multi-institutional studies that examine effects at multiple levels, from the learner to the team, the institution, and the health care system. Such a framework of research questions can guide and facilitate scholarly discourse on the theoretical and practical body of knowledge related to competency-based health professions education.